The Science of Homeopathy in Relevance to Dentistry: A Comprehensive Review - Adaki, Shridevi; Karagir, Amol; Adaki, Raghavendra; Vanaki, Bhagyashree; Sale, Sheetal; Bijjal, Anupama (Journal of Neonatal Surgery, 2025)
Homeopathy, a holistic system of medicine based on the principle of "like cures like," has been widely used in various medical fields, including dentistry. With the growing emphasis on minimally invasive and patient-centered care, homeopathy is gaining attention as a complementary treatment modality for managing dental conditions. However, its mechanisms of action and clinical efficacy remain subjects of scientific debate. This review aims to explore the scientific principles underlying homeopathy, its proposed mechanisms of action, and its clinical applications in dentistry. By analyzing recent literature and clinical evidence, this article seeks to provide an evidence-based perspective on the role of homeopathy in modern dental practice. While homeopathy presents a promising complementary approach in dentistry, further research is necessary to establish its efficacy through rigorous scientific studies. Collaborative efforts between dental and homeopathic practitioners can pave the way for integrative treatment models that prioritize holistic patient care. As evidence continues to evolve, homeopathy may offer valuable adjunctive benefits in dental practice, particularly for patients seeking natural and minimally invasive therapies.